Managing Inter-Organizational Relationships in Non-Governmental Development Organizations - Meyer, Marie (2009)
This paper examines the issues in the management of partnerships between non-governmental organizations and their commercial and institutional partners. In the light of the changes in the non- profit sector environment, the paper presents the evolution of the partnerships from a funder-receiver relationships toward more reciprocity. Based on the case study of a development NGO in France, it argues that the evolution of IORs is driven by a need for efficiency and legitimacy from the part of NGOs and results in a greater commitment of the whole society to the development problematic. Recommendations are drawn for other NGOs to build closer partnerships and to turn outward to their environment.